APLIKASI PEMBELAJARAN ILMU TAJWID BERBASIS ANDROID - Sardi, Yumi (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2014)
Technology is developing very rapidly in this era of modernization, mobile technologies that today are not only used as a communication tool, but also as a tool to facilitate the user in everyday life. Tajwid has a very important role in the reading of Al-Qurâan. Tajwid is one science that studies how to pronounce or sounding the letters contained in the Al-Qurâan properly. One of them know and master tajwid properly, neglected and even forgotten. One contributing factor is the limitation of time and space as well as supervising teacher is still a major obstacle in learning tajwid. The study was conducted easier for people Muslimin and musliman in studying recitation. This application will display a laws of Tajwid and recitation example, using the Android application is the application of tajwid can guide the user in lafadz tajwid learn and pronounce correctly without limiting the time and place where they are.Keywords:Â Applications, learning, science, tajwid, based, Android.